Gut microbiota and gastrointestinal health: current concepts and future directions. Issue 1 (20th December 2012) - Aziz, Q.; Doré, J.; Emmanuel, A.; Guarner, F.; Quigley, E. M. M.
Abstract: Background The microbial community of the human gut – the enteric microbiota – plays a critical role in functions that sustain health and is a positive asset in host defenses. In recent years, our understanding of this so‐called human 'super organism' has advanced, following characterization of fecal metagenomes which identified three core bacterial enterotypes, and based on basic and clinical research into the impact and consequences of microbiota biodiversity and change on gastrointestinal disorders and diseases. Purpose This article considers current knowledge and future perspectives on the make‐up and function of human gut microbiota, with a particular focus on altered microbiota and gastrointestinal disorders, nutritional influences on the gut microbiota, and the consequences for gastrointestinal health, as well as improved understanding of gut‐microbiota–brain communication.